Landscape Ecology for Sustainable Environment and Culture - Fu, Bojie; Jones, K. Bruce; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Climate change and the pressures of escalating human demands on the environment have had increasing impacts on landscapes across the world. In this book, world-class scholars discuss current and pressing issues regarding the landscape, landscape ecology, social and economic development, and adaptive management. Topics include the interaction between landscapes and ecological processes, landscape modeling, the application of landscape ecology in understanding cultural landscapes, biodiversity, climate change, landscape services, landscape planning, and adaptive management to provide a comprehensive view that allows readers to form their own opinions. Professor Bojie Fu is an Academician of Chinese Academy of Sciences and Chair of scientific committee at the Research Center for Eco-Environmental Sciences, Chinese Academy of Sciences, Beijing, China. Professor K. Bruce Jones is the Executive Director for Earth and Ecosystem Sciences Division at Desert Research Institute, University of Nevada, Las Vegas, USA.
Part I Concepts and Approaches -- Part II Landscape Modeling -- Part III Landscape Planning and Management.
Keywords: Life sciences; Regional planning; Biodiversity; Landscape ecology; Environmental management; Nature Conservation; Sustainable development; Life Sciences; Landscape Ecology; Sustainable Development; Landscape/Regional and Urban Planning; Nature Conservation; Biodiversity; Environmental Management